Cover Image. Issue 10 (26th April 2022) - Wang, Jia‐Bo; Huang, Ang; Wang, Yijin; Ji, Dong; Liang, Qing‐Sheng; Zhao, Jun; Zhou, Guangde; Liu, Shuhong; Niu, Ming; Sun, Ying; Tian, Hui; Teng, Guang‐Ju; et al.
Abstract : The cover image is based on the Randomised Clinical Trial Corticosteroid plus glycyrrhizin therapy for chronic drug‐ or herb‐induced liver injury achieves biochemical and histological improvements: A randomised open‐label trial by Jia‐Bo Wang et al., https://doi.org/10.1111/apt.16902 .